Experimental Investigation of the Dynamic Response of Squeeze Film Dampers Made of Steel and Glass/Epoxy - Waleed F. Faris; Asad A. Khalid; A. Albagul; Godem A. Ismail (Shock and Vibration)
This work is devoted to the fabrication and investigation of the Squeeze Film Dampers (SFDs) which are widely used in many applications. This include the fabrication of a test rig and several dampers with different sizes and two different materials which composite and non-composite. Composite dampers (Glass/epoxy), each consists of 30 layers, were fabricated by hand lay-up method. Outer and inner diameters of all the fabricated dampers were maintained as 60 and 40 mm respectively. Non-composite dampers (Steel) were fabricated and tested using turning machine. Three dampers of different lengths were examined for both materials. A rotor-bearing system for the analysis has been designed and fabricated. The test rig consists of mild steel shaft, two supports, oil pressure system, and two self-alignment ball bearings were fixed on each end support. Two squeeze film dampers were used for the two support ends. Vibration amplitude has been examined for all the fabricated dampers at different shaft rotational speeds. The first resonance speed was examined for all the dampers tested. Results show that the vibration amplitude of the steel damper was lower than Glass/epoxy dampers with the same L/D ratio. On the other hand, a considerable weight saving has been achieved by using Glass/epoxy composite dampers. It has been found that the performance of squeeze film damper improved with increasing length/diameter ratio (L/D) within the range tested.